Psychogenic and neurogenic components in patients with psychogenic or neuropathic pruritus: PRURINEURO: A non‐interventional single‐centre prospective assay - Marie Orliaguet; Emilie Brenaut; Anne‐Sophie Ficheux; Sylvie Boisramé; Laurent Misery (Wiley, 2023)
Abstract Background The causes of pruritus are multiple and commonly classified into six different categories: dermatological, systemic, neuropathic, psychogenic, mixed and idiopathic. In clinical practice, psychogenic and neurogenic mechanisms tend to be separated in the etiological diagnosis of neuropathic or psychogenic disorders; nevertheless, studies investigating the respective psychogenic and neurogenic components are lacking. Objective The main objective of this work was to highlight the differences and potential common characteristics between psychogenic pruritus and neuropathic pruritus. Methods This study was a noninterventional single‐centre prospective assay. Patients with neuropathic (NP) or psychogenic (PP) pruritus were proposed to participate. The psychogenic and neurogenic components of pruritus in these patients were evaluated using six validated questionnaires or criteria, namely, the diagnosis criteria of psychogenic pruritus, the NP5 questionnaire, the Brest Pruritus Qualitative Assessment Questionnaire, Hospital Anxiety and Depression Scale, Toronto Alexithymia Scale, and DN4i. Results Twenty‐five patients with NP and 15 with PP were included. A difference between the two groups was observed for NP5, with mean scores of 2.8 ± 0.9 and 1.4 ± 1 for the NP and PP groups, respectively (p < 0.0001). For depression, the average score was 3.5 ± 3.9 for the NP group and 7.5 ± 5.1 for the PP group (p < 0.02). Conclusion While neuropathic and psychogenic disorders are different diagnoses, neuropathic and psychogenic components may exist simultaneously in patients with NP or PP.